2006
DOI: 10.4141/p05-102
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting inter-organismal chemical communication for improved inoculants

Abstract: [951][952][953][954][955][956][957][958][959][960][961][962][963][964][965][966]. The combination of rising fossil fuel prices and a need to reduce greenhouse gas emissions will lead to expanded use of crop inoculants (bio-fertilizers) both for increased production of biomass (for bio-fuels and soil C storage) and to reduce production of nitrous oxide, through increased reliance on biological nitrogen fixation. Over the last century inoculants have been improved through strain selection, improved carriers (inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 99 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…At a time when we are concerned about the environmental impacts of pesticides (Busby et al, 2017) and extensive fertilizer application, PGPR and microbe-to-plant signal molecules offer alternative strategies for increasing, or at least maintaining, crop yields with reduced pesticide and fertilizer inputs while developing more climate change-resilient agricultural systems. There is enormous potential in our ability to manipulate the phytomicrobiome and its signals, as our understanding of this very complex system grows (Mabood et al, 2006a;Schlaeppi and Bulgarelli, 2015;Smith et al, 2015b;Gopal and Gupta, 2016;Głodowska et al, 2017;Lamont et al, 2017;Wallenstein, 2017). In addition, LCO and thuricin 17 are effective at very low concentrations (LCOs: 10 −6 -10 −8 M, thuricin 17: 10 −9 -10 −11 M; Smith et al, 2015a,b;Subramanian and Smith, 2015) and are inexpensive to produce.…”
Section: Contribution Of the Phytomicrobiome To Global Food Securitymentioning
confidence: 99%
“…At a time when we are concerned about the environmental impacts of pesticides (Busby et al, 2017) and extensive fertilizer application, PGPR and microbe-to-plant signal molecules offer alternative strategies for increasing, or at least maintaining, crop yields with reduced pesticide and fertilizer inputs while developing more climate change-resilient agricultural systems. There is enormous potential in our ability to manipulate the phytomicrobiome and its signals, as our understanding of this very complex system grows (Mabood et al, 2006a;Schlaeppi and Bulgarelli, 2015;Smith et al, 2015b;Gopal and Gupta, 2016;Głodowska et al, 2017;Lamont et al, 2017;Wallenstein, 2017). In addition, LCO and thuricin 17 are effective at very low concentrations (LCOs: 10 −6 -10 −8 M, thuricin 17: 10 −9 -10 −11 M; Smith et al, 2015a,b;Subramanian and Smith, 2015) and are inexpensive to produce.…”
Section: Contribution Of the Phytomicrobiome To Global Food Securitymentioning
confidence: 99%
“…These include bacteria in the soil near plant roots, on the surface of plant root systems, in spaces between root cells or inside specialized cells of root nodules; they stimulate plant growth through a wide range of mechanisms ( Gray and Smith, 2005 ; Mabood et al, 2014 ), such as: (1) nutrient solubilization (particularly phosphorus – Boddey et al, 2003 ; Kennedy et al, 2004 ; Trabelsi and Mhamdi, 2013 ), (2) production of metal chelating siderophores, (3) nitrogen fixation ( Vessey, 2003 ; Bhattacharyya and Jha, 2012 ; Drogue et al, 2012 ), (4) production of phytohormones, (5) production of 1-aminocyclopropane-1-carboxylate deaminase, (6) production of volatile organic compounds, (7) induction of systemic resistance [induced systemic resistance (ISR) and systemic required resistance (SAR) – Jung et al, 2008b , 2011 ], and (8) suppression of disease through antibiosis ( Bhattacharyya and Jha, 2012 ; Spence et al, 2014 ). It has also been shown that “signal” compounds produced by bacteria in the phytomicrobiome stimulate plant growth ( Prithiviraj et al, 2003 ; Mabood et al, 2006a ; Lee et al, 2009 ), particularly in the presence of abiotic stress ( Wang et al, 2012 ; Subramanian, 2014 ; Prudent et al, 2015 ). In the broadest sense PGPR include legume-nodulating rhizobia.…”
Section: The Phytomicrobiome and Plant Growthmentioning
confidence: 99%
“…That plants and microbes use signal compounds to communicate during establishment of beneficial plant-microbe interactions ( Desbrosses and Stougaard, 2011 ), is well-described for the legume-rhizobia nitrogen fixing symbiosis ( Oldroyd et al, 2010 ; Giles et al, 2011 ; Oldroyd, 2013 ), and somewhat elucidated for mycorrhizal associations ( Gough and Cullimore, 2011 ). In the legume-rhizobia relationship the plant releases flavonoid signals to rhizobia ( Hassan and Mathesius, 2012 ) or, in some cases, jasmonate signals ( Mabood et al, 2006a , b ; Mabood et al, 2014 ), followed by rhizobial production of lipo-chitooligosaccharides (LCOs) as return signals ( Oldroyd, 2013 ). The LCOs are bound by LysM receptors, which have kinase activity ( Antolin-Llovera et al, 2012 ), changing root hormone profile ( Zamioudis et al, 2013 ) and triggering development of root nodules.…”
Section: Signaling In the Phytomicrobiomementioning
confidence: 99%
“…Mineral fertilizers, while increasing yield, have contributed to environmental problems related to leakage of nutrients out of the soil to the environment, such as nitrous oxide emission to the atmosphere and eutrophication of water bodies. These inoculants may include bioactive molecules, sometimes called signal molecules, to improve symbiotic formation and function (Mabood et al 2006). These inoculants can maximize crop yields and quality while minimizing applications of chemical fertilizers and pesticides that can be harmful to people and the environment.…”
Section: Symbiotic Fungi Biotechnologymentioning
confidence: 99%